HARAPAN IBU TERHADAP ASUHAN SAYANG IBU OLEH BIDAN SELAMA PROSES PERSALINAN - Nuryanti Zulala, Nuli; Herfanda, Esitra (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Labor is a transformational process for women, where women have different expectations in the labor process. Identifying the hopes, desires, needs, and fears of the women for the labor process will make the birth attendant provide services and positive labor experience for the women. The Expectations during labor process has an important role in determining the response of the women to the experience of labor. Women want a positive labor experience that matches or even exceeds their expectations and beliefs. Midwives care for women have affects both physically and psychologically in the short and long term. Objective: This qualitative research aims to find out the expectation of mothers in the care of mothers by midwives during the labor process. Methods: in-depth interviews with 4 postpartum mothers’s regarding their expectations of midwives care during labor. Result and Conclution: There were 3 themes of mother's expectation in labor process : the comfort of labor, the safety of labor and support during labor.